Monte carlo simulation of different positron emitting radionuclides incorporated in a soft tissue volume / Simulación de Monte carlo de diferentes radionúclidos emisores de positrones incorporados en un volumen de tejido blando - Martínez Ovalle, Segundo Agustín; Olaya Dávila, Hernan; Castro Serrato, Hector Fabio (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Monte Carlo calculations were carried out where compounds with positron-emitters radionuclides, like FDG (18F), Acetate (11C), and Ammonium (13N), were incorporated into a soft tissue volume, in the aim to estimate the type of particles produced their energies, their mean free paths, and the absorbed dose at different distances with respect to the center of the volume. The volume was modeled with a radius larger than the maximum range of positrons in order to produce 0.511 keV annihilation gamma-ray photons. With the obtained results the absorbed dose, in various organs and tissues able to metabolize different radiopharmaceutical drugs, can be estimated. The code used was GEANT4.